Information system’s impact on shift leaders’ indoor movement in emergency departments - Ren, Zhuqing (My University, 2021)
Objective To explore the movement of shift leaders before and after the implementation of the Columna Clinical Logistics system in emergency department. Methods This study is a sub-study of the AKUVATYHO study of the Connected Health Research Group of the UTU. This research focuses on the impact of the CCL system on nursing and physician shift leaders’ indoor movement using secondary data analysis base on a retrospective study design. A non-probability sampling method was used to select three EDs in Finnish hospitals. A time motion study' s automatic indoor positioning data collection technology was used in the study. A Bluetooth-based indoor positioning system was placed in all three EDs included in the study to record the number of times the shift leaders visited each room in the three EDs and the time for how long they stayed in each of these rooms. The statistical units are the monthly average number. The three units were: 1) Control unit A, which did not have the CCL information management system. A total of 31 Bluetooth beacons were placed in this unit; 2) Control unit B, which had implemented the CCL information management system prior to this study. There, 39 Bluetooth beacons were placed; 3) The intervention unit, which implemented the CCL information management system during the study. The intervention unit had 24 Bluetooth beacons in place. Data were collected simultaneously around the clock in all three participating units for four weeks at the time during five intervals from June 2015 to December 2016. Two of the data collection intervals were pre-implementation and three were post-implementations of the CCL. Ethical review was done at UTU Ethics Committee (ref: 39/2015) and research approvals were obtained from each participating hospital district. The data has been stored in an JSON format in a database. The new Excel format database is obtained by extracting relevant variable data (shift, profession, timepoint and room) from the database of the previous AKUVATYHO study. When extracting data, it has been double checked by two information science experts to ensure the accuracy of the new database input used in this study. All data were processed with the statistical software JMP, version 15. The statistical methods included descriptive statistical analysis, Kruskal-Wallis H test and Stell-Dwass test. Results: This study showed that there were differences in the stay time and the number of visits in rooms between the control units. The differences were: ① The ED shift leaders of control unit B had fewer visits of in each room in the ED than control unit A (11260 times vs. 26229 times). A statistically difference was in the number of visits of the observation room (p = 0.0051) by nurse shift leader in both shifts (office hour and on-call hour). A statistically difference was in the number of visits in the procedure room (p<0.0001) by both of the profession and shifts. In triage, the number of visits in (p=0.0163) by nurse shift leader during on-call hour had a statistically difference. ② ED shift leaders' stay time in the procedure room of the control unit B (3434.3 minutes) was shorter than in the control unit A (6303.7 minutes). A statistically difference shown in ED shift leaders’ stay time in the procedure room (p = 0.0176) by nurse shift leader in both of the shifts. A statistically difference shown in ED shift leaders’ stay time in the observation room (p <0.001) by both profession and in both of the shifts. In the intervention unit, the results of ED shift leaders' movement were different before and after implemented the CCL system. The differences were: ①Before using CCL system, the median value of visits per room by ED shift leaders was 58 times, which is more than the CCL system implemented (56 times). The mean value of stay time per room was also decreased after implementation of the CCL system (206.8 minutes vs. 150.6 minutes). ②A statistical difference was seen in the nurse shift leaders’ movement during on-call hours (p<0.0193) before and after system implementation. Findings showed that the nurse shift leader saved 14.1 minutes of staying in the observation room (p<0.495), 44 minutes of staying in patient rooms (p<0.0304) and 76.6 minutes of staying in triage (p<0.0495) during on-call hours after CCL implementation. Conclusion: Most of the significant differences regard nurse shift leader during on-call hours between the unit that has used CCL for many years (unit B) and the unit without such a system (unit A). There were differences in the intervention unit when comparing the time before and after CCL implementation. In the statistical analysis, the movement of nurse shift leaders during on-call hours had statistical differences. CCL system implementation has changed the movement of ED nurse shift leaders in number of visit and stay time in triages, observation rooms and patient rooms during on-call hours. The result showed the nurse shift leader's movement has been reduced and it saved ED nurse shift leaders' time during on-call hours in triages, observation rooms and patient rooms. However, these findings must be interpreted with caution due to the limitations. To validate these findings, we need more research.
Keywords: emergency department, information system, shift leader, operations management